The demand for public goods in India: an empirical test of Wagner's Law. - Huq, Faizul; Huq, Ziaul; Chakravarty, Ranjan; Zakaullah Shariff, Mohammad (CIENCIA ergo-sum, 2017)
The public sector has become increasingly important in the modern mrket economies of today. According to Adolph Wagner (1959), at any given time public expenditures reflect the requirements of the prevailing economic situation in a country. Changes in these expeditures signals structural changes in the ntional economy. Wagner based this on the income elasticies of demand for services provided by the government, and the encroachment of the public sector on the private sector in the course of economic development. The focus of this study on the income elasticies of demand for public goods in India is conducted for the 1955-1983 post-independence period. The second consideration follows the income elasticity test thus completing an empirical test of Wagner's Law.